PREPARATION AND STRATEGIES APPLIED BY TEACHERS OF MATH AND SCIENCE IN ENGLISH OF BILINGUAL PROGRAM AT ELEMENTARY SCHOOL - Masruddin Masruddin (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2014)
This paper is focused on the teachers at elementary school who teach other subjects in English namely math and science at bilingual class program. The main matter is what are their strategy in preparing their selves to teach other subjects. And how they solve the problem and difficulties during the teaching other subjects. This research can be a good share and information about helping teachers teach other subject in English. This is a qualitative research. There are 2 teachers as respondent of this research. They are observed and interviewed. Then, the data are analyzed descriptively. The data are categorized and percentage. Finally the data were discussed. The result of this research shows that both of the teachers do some preparation before presenting the material in English such as make some notes on important vocabulary that will be taught in the class. The, the way they handle the problem by repeating some instruction in order to make the information reached the point. In addition, they need to arrange their lesson plan well in terms of bilingual action in English and Indonesia. They have to consider many aspects of students condition and their need in the subject.